Financial performance (dis)parity in post-transition Europe - Lorena Mošnja-Škare (Contemporary Economics, 2024)
This work is licensed under a Creative Commons Attribution 4.0 International License. Decades after the transition processes have spread across Central, Eastern, and South-Eastern Europe (CESEE), the former Soviet Union, and the Baltic, it was interesting to perform the post-transition and non-transition advanced European economies comparison to capture the outcomes of the 'catching-up process' . In this analysis, I tried to reach the results of this 'catching process' using the firm-level accounting data, namely, enterprises' annual accounts rather than countries' national accounts. The goal was to evaluate if post-tran- sition countries' enterprises have reached the financial performance of non-transition countries' enterprises across Europe, three decades after the transition processes began. The research captured firm-level financial performance aspects revealing some differentiators, namely, financial report indicators that differed for the enterprises belonging to post-transition countries in comparison with the ones belonging to non-transition countries in Europe. The findings related to the liquidity, solvency, indebtedness, profitability indicators, and labor intensity ratio were derived by logit regression models. The observations for 569 European companies were provided by Orbis Europe for the year 2021 annual accounts. According to the results, enterprises in post-transition countries, characterized by lower total assets and working capital scale, were likely to have lower profit margins, share of employees' costs in operating turnover, current ratio, and gearing, while higher solvency and liquidity ratio. Mild marginal effects indicated the gap narrowed but with still existing significant disparities, particularly in the field of liquidity.
Keywords: M41; G30; P27; 330; financial indicators; annual accounts; financial performance; transition